2009
DOI: 10.1080/00103620902960583
|View full text |Cite
|
Sign up to set email alerts
|

Mycorrhiza Effect on Maize P Uptake from Phosphate Rock and Superphosphate

Abstract: Low available phosphorus (P) is a serious constraint for crop production in acidic tropical soils. Economical yields in these environments require application of large amounts of costly nitrogen (N) and P fertilizers. Although phosphate rock (PR) has been proposed as a less expensive P source, the slow P release to the soil limits its use for annual crops. The objective of this work was to examine the effect of inoculating a nonsterile acidic soil with vesicular arbuscular mycorrhizal (VAM) Gigaspora margarita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…Burghelea et al (2015) observed in a similar approach as ours, that over 124 days, AM mycorrhized plant growth was enhanced in presence of rhyolite rocks, due to an efficient P mining. Different authors have demonstrated the ability of AMF to mobilize P from AP, e.g., Rhizophagus fasciculatus and Rhizophagus tenuis (Powell and Daniel 1978), Rhizophagus manihotis (Ness and Vlek 2000), Rhizophagus clarum (Alloush and Clark 2001), and Gigaspora margarita (Ramirez et al 2009), and Koele et al (2014) (mean values ± standard error, n = 3). Within each P source and day, treatments with significant differences are indicated by different small letters (p < 0.05) as analyzed by one-way ANOVA.…”
Section: Methodsmentioning
confidence: 99%
“…Burghelea et al (2015) observed in a similar approach as ours, that over 124 days, AM mycorrhized plant growth was enhanced in presence of rhyolite rocks, due to an efficient P mining. Different authors have demonstrated the ability of AMF to mobilize P from AP, e.g., Rhizophagus fasciculatus and Rhizophagus tenuis (Powell and Daniel 1978), Rhizophagus manihotis (Ness and Vlek 2000), Rhizophagus clarum (Alloush and Clark 2001), and Gigaspora margarita (Ramirez et al 2009), and Koele et al (2014) (mean values ± standard error, n = 3). Within each P source and day, treatments with significant differences are indicated by different small letters (p < 0.05) as analyzed by one-way ANOVA.…”
Section: Methodsmentioning
confidence: 99%
“…Ramirez et al (2009) also reported a reduction in maize growth in response to RP application and a reversal of the effect by inoculation of the AM fungus Gigaspora margarita W.N. Becker & I.R.…”
Section: Discussionmentioning
confidence: 99%
“…These Ca-phosphate species are often denoted by the term rock phosphates if they originate from a marine diagenetic mineral deposit [4,22]. A number of plant-mycorrhiza studies have demonstrated that AMF can successfully mobilize the phosphorus in apatites or at least, can significantly contribute to the solubilization of these P minerals, e.g., Glomus manihotis [25]; Glomus fasciculatus and Glomus tenuis [26], Glomus clarum [27] and Glomus margarita [28]. In root organ cultures it was shown that the extraradical mycelium (ERM) of Rhizophagus irregularis (formely known as Glomus intraradices) was able to release orthophosphate from hydroxyapatite, and to a lesser extent, also from a low-reactive rock phosphate mineral [29].…”
Section: Introductionmentioning
confidence: 99%